ANALISIS PERLAKUAN AKUNTANSI UANG MUKA MURABAHAH PADA BANK KALSEL CABANG SYARIAH BANJARMASIN - HARIYANTO, HARIYANTO (At-Taradhi Jurnal Studi Ekonomi, 2015)
Abstract: This study aimed to analyze the accounting treatment applied murabaha advance by BankSyariah Branch South Kalimantan Banjarmasin, both as buyers and as sellers are in accordance with theFatwa DSN, IAS, and PAPSI. This research is a field that is qualitative research, where researchers usedinterviews and documentation. The results showed that the share of advances at Bank Syariah BranchSouth Kalimantan Banjarmasin determined based on the price of the goods and the condition of thegoods. advances are recognized as part of the payment of Murabahah receivables. advances that areapplied by the Bank of South Kalimantan Banjarmasin have within their Sharia Fatwa DSN, IAS, andPAPSI. No down payment for second variation, the first customers pay a deposit to the bank, and thesecond customer to pay an advance directly to the supplier using wakalah.